Have a little faith : a true story - Albom, Mitch, 1958- (Hyperion, 2009)
When an eighty-two-year-old rabbi from Albom's old hometown asks him to deliver his eulogy, Albom goes back to his nonfiction roots and becomes involved with a Detroit pastor (a reformed drug dealer and convict) who preaches to the poor and homeless in a decaying church with a hole in its roof. This is a timely, moving, and inspiring look at faith--not just who believes, but why.